2013
DOI: 10.1073/pnas.1221297110
|View full text |Cite
|
Sign up to set email alerts
|

Probing vasoocclusion phenomena in sickle cell anemia via mesoscopic simulations

Abstract: Vasoocclusion crisis is a key hallmark of sickle cell anemia. Although early studies suggest that this crisis is caused by blockage of a single elongated cell, recent experiments have revealed that vasoocclusion is a complex process triggered by adhesive interactions among different cell groups in multiple stages. However, the quantification of the biophysical characteristics of sickle cell anemia remains an open issue. Based on dissipative particle dynamics, we develop a multiscale model for the sickle red bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 39 publications
(32 reference statements)
2
86
0
Order By: Relevance
“…Recent studies suggest that RBC aggregation properties are likely to be involved in the pathophysiology of SCA [32], and the force required to disrupt aggregates of RBCs in case of SCA is around four times greater than that in the healthy RBC [33]. The RBC aggregation interactions are modelled by the Morse potential with the following properties [24,27] With the parameters defined as shown above, we first consider the healthy blood. The measured shear viscosity with respect to shear rate is plotted in figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that RBC aggregation properties are likely to be involved in the pathophysiology of SCA [32], and the force required to disrupt aggregates of RBCs in case of SCA is around four times greater than that in the healthy RBC [33]. The RBC aggregation interactions are modelled by the Morse potential with the following properties [24,27] With the parameters defined as shown above, we first consider the healthy blood. The measured shear viscosity with respect to shear rate is plotted in figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…This can be confirmed by the studies of Xiong and Tukin which revealed that in case the stiffness of cell membranes increases, blood flow in microvessels is bothered. [4,5,7] In the studies of Zuk et al, it was also found out that an increase in the erythrocyte elastic modulus worsens the ability of a cell to bind oxygen and transport it through capillaries. [1,7,15] It is known that blood cells suspended in plasma or physiological salt solution (erythrocytes, platelets and leukocytes) carry a negative charge at their physiological pH, which ensures their normal functioning.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] The parameters of the erythrocyte geometry characterize the properties of red cells to deform under external impact and to change the viscous properties of blood, which largely determines the quality of capillary blood flow and indicates a certain change in the rheological properties of the blood. [1,[5][6][7] In this regard, the study of structural and metabolic status of red blood cells of chickens when adapting to production factors is not only of scientific but also of practical interest.…”
mentioning
confidence: 99%
“…These simulations involved the simulation of sickle cell adhesion to a wall with a simulation of the flow of blood cells in the vessel at a hematocrit approaching that of blood using a particle dissipation method. The simulation address the conditions of sickle cell shape, adhesiveness and elasticity that can cause the occlusion of a small blood vessel, resulting in a vasal occlusion crisis [55].…”
Section: Blood Cell Adhesionmentioning
confidence: 99%